pengaruh keadilan organisasi terhadap kepuasan kerja dan turnover intention pada karyawan Oberoi hotel Bali - Wedantha, Ida Bagus; Supartha, Wayan Gede (E-Jurnal Manajemen, 2016)
This study aims to determine the effect of organizational justice on job satisfaction and turnover intention of employees Oberoi Hotel Bali in Seminyak, Kuta. The population used in this study were all employees Oberoi Hotel Bali which amounted to 140 people. The sampling method in this research is done with probability sampling approach because the sample frame is already known such as number of employees, while the sampling method used in this study refers to slovin approach. Based on these criteria the number of employees who qualify as a sample of 58 employees. The analysis tool used is the technique of path analysis (path analysis). The results obtained in this study is justice organization and a significant negative effect on turnover intention, job satisfaction and a significant negative effect on turnover intention, as well as organizational justice positive and significant effect on job satisfaction. Keywords: Organizational Justice, Job Satisfaction, Turnover Intention